Clinical-radiomics-based treatment decision support for KIT Exon 11 deletion in gastrointestinal stromal tumors: a multi-institutional retrospective study - Zhang, Yu; Yue, Xiaofei; Zhang, Peng; Zhang, Yuying; Wu, Linxia; Diao, Nan; Ma, Guina; Lu, Yuting; Ma, Ling; Tao, Kaixiong; Li, Qian; Han, Ping (Frontiers in Oncology, 2023)
Objective: gastrointestinal stromal tumors (GISTs) with KIT exon 11 deletions have more malignant clinical outcomes. A radiomics model was constructed for the preoperative prediction of KIT exon 11 deletion in GISTs.Methods: Overall, 126 patients with GISTs who underwent preoperative enhanced CT were included.GISTs were manually segmented using ITK-SNAP in the arterial phase (AP) and portal venous phase (PVP) images of enhanced CT. Features were extracted using Anaconda (version 4.2.0) with PyRadiomics. Radiomics models were constructed by LASSO. The clinical-radiomics model (combined model) was constructed by combining the clinical model with the best diagnostic effective radiomics model. ROC curves were used to compare the diagnostic effectiveness of radiomics model, clinical model, and combined model. Diagnostic effectiveness among radiomics model, clinical